Effect of Low Degradable Sunflower Meal and Seed on Growth, Some Carcass and Blood Measurements in Awassi Lambs - Shehab, Safwan Luqman; Mohammed, Omar Dheyaa; Ahmed, Falah Hassan (Journal of agricultural, environmental and veterinary sciences, 2021)
The study was conducted to investigate the effect of lowering protein degradability in sunflower meal or protein and fat in sunflower seeds on performance and carcass parameters. Sixteen Awassi lam. sixteen Awassi lambs were used with an average weight (28.37 ± 0.80 kg) , aged 3.5-4 months , lambs were divided into four groups, the first group fed on a diet sunflower cake contained 11% of its components, the second group fed on a diet similar to the first group, except that the sunflower cake was low degradable, the third group was fed on a diet contained 11% sunflower seed as a substitute for sunflower cake, while the fourth group fed a diet containing 11% low degradable Sunflower seed. The results indicated that feeding the low degradable sunflower cake in the second group led to a significant increase (p <0.05) in slaughter weight 45.56 kg and total gain 16.93 kg compared with the third group which fed sunflower seed 42.93 and 14.68 kg respectively. The lowest (p <0.05) hot carcass weight was recorded in the third group 22.43 kg as compared to the first and second groups 24.07 and 24.27 kg respectively. Also, body wall thickness was increase and back fat thickness decrease (p <0.05) in the second group compared with other groups. The results of blood measurements were indicated that total protein increased significantly (p <0.05) in the fourth group 7.13 g/100 ml compared with first group 6.56 g/100 ml, blood urea concentration was significantly lower (p <0.05) with feeding sunflower seeds 28.25 and 28.19 mg/ 100 ml as compared with second group that fed a low degradable sunflower cake 34.18 mg/ 100 ml.